C(sp3)–H oxygenation via alkoxypalladium(ii) species: an update for the mechanism. Issue 5 (20th January 2022) - Zhang, Shuaizhong; Zhang, Jinquan; Zou, Hongbin
Abstract : Alkoxypalladium(ii ) species lead to γ-C(sp 3 )–H acyloxylation and alkoxylation products using tert -butyl hydroperoxide as the oxidant. Abstract : Pd-catalyzed C(sp 3 )–H oxygenation has emerged as an attractive strategy for organic synthesis. The most commonly proposed mechanism involves C(sp 3 )–H activation followed by oxidative addition of an oxygen electrophile to give an alkylpalladium(iv ) species and further C(sp 3 )–O reductive elimination. In the present study of γ-C(sp 3 )–H acyloxylation of amine derivatives, we show a different mechanism when tert -butyl hydroperoxide (TBHP) is used as an oxidant—namely, a bimetallic oxidative addition-oxo-insertion process. This catalytic model results in an alkoxypalladium(ii ) intermediate from which acyloxylation and alkoxylation products are formed. Experimental and computational studies, including isolation of the putative post-oxo-insertion alkoxypalladium(ii ) intermediates, support this mechanistic model. Density functional theory reveals that the classical alkylpalladium(iv ) oxidative addition pathway is higher in energy than the bimetallic oxo-insertion pathway. Further kinetic studies revealed second-order dependence on [Pd] and first-order on [TBHP], which is consistent with DFT analysis. This procedure is compatible with a wide range of acids and alcohols for γ-C(sp 3 )–H oxygenation. Preliminary functional group transformations of the products underscore the great potential of this protocol for structural manipulation.